The Clinical Role of Glutamine Supplementation in Patients with Multiple Trauma: A Narrative Review. Issue 1 (January 2013) - Al Balushi, R. M.; Cohen, J.; Banks, M.; Paratz, J. D.
Glutamine is considered an essential amino acid during stress and critical illness. Parenteral glutamine supplementation in critically ill patients has been shown to improve survival rate and minimise infectious complications, costs and hospital length-of-stay. However, glutamine supplementation in patients receiving enteral nutrition and the best method of administration are still controversial. The purpose of this article is to provide a narrative review of the current evidence and trials of enteral and parenteral glutamine supplementation in multiple trauma patients. A search in PubMed and EMBASE was conducted and relevant papers that investigated the effect of enteral or parenteral glutamine supplementation in patients with multiple trauma were reviewed. Although recent nutritional guidelines recommend that glutamine supplementation should be considered in these patients, further well-designed trials are required to provide a confirmed conclusion. Due to the inconclusive results of enteral glutamine supplementation trials in patients receiving enteral nutrition, future trials should focus on intravenous glutamine supplementation in patients requiring enteral nutrition and on major clinical outcome measures (e.g. mortality rate, infectious complications).